Sikap prososial pada remaja di Surabaya: Bagaimana peranan implementasi nilai-nilai kebangsaan? (SUKMA : Jurnal Penelitian Psikologi, 2021)
This study aims to determine the relationship between national values and adolescent prosocial attitudes in Surabaya. National values are the values inherent in every city or the norms of goodness that are contained and characterize the personality of the Indonesian people, which are derived from the values of Pancasila, the 1945 Constitution, the Unitary State of the Republic of Indonesia, and Bhinneka Tunggal Ika. Prosocial behavior is an act that benefits others but does not provide a real advantage for the person performing the action. This study examined the value of nationality as the independent variable and prosocial attitudes as the dependent variable. The hypothesis in this study is that there is a relationship between national values and prosocial attitudes in adolescents. The participants of this study were adolescents who go to school in Surabaya with an age range of 14 to 18 years, with a total of 107 participants. Thissstudyhusesra a quantitative approach to test the proposed research hypothesis. Data analysis techniques used the Spearman's Rho test with the help of the Statistical Package for the Social Sciences (SPSS) program version 16.0 for windows. The results of the correlation analysis between the variable national values and prosocial attitudes using Pearson obtained a score of rxy = 0.866 with a significance of p = 0.000 (p> 0.05). This means that there is a significant relationship between the variable national values and prosocial attitudes. Penelitian mempunyai tujuan untuk mengetahui hubungan antara implementasi nilai-nilai kebangsaan dengan sikap prososial remaja di Surabaya. Nilai kebangsaan adalah nilai yang melekat pada warga negara yang mengandung berbagai norma kebaikan serta kepribadian bangsa yang bersumber dari pancasila dan undang-undang dasar tahun 1945 Bhinneka Tunggal Ika. Perilaku prososial adalah tindakan untuk membantu atau menolong orang lain tanpa mempertimbangkan keuntungan bagi yang melakukan tindakan tersebut. Penelitian ini menguji nilai kebangsaan sebagai variabel bebas dan sikap prososial sebagai variabel terikat. Hipotesis dalam penelitian ini ialah terdapat hubungan antara nilai kebangsaan dengan sikap prososial pada remaja. Partisipan penelitian ini adalah remaja yang bersekolah di Surabaya dengan rentang usia 14 s/d 18 tahun yang bejumlah 107 partisipan. Penelitian ini menggunakan pendekatan kuantitatif untuk menguji hipotesis penelitian yang diajukan. Teknik analisis data menggunakan uji Spearman’s Rho dengan memanfaatkan bantuan program Statistical Package for the Social Sciences (SPSS) versi 16.0 for windows. Hasil analisis korelasi antara variabel nilai kebangsaan dengan sikap prososial menggunakan Pearson diperoleh skor rxy=0.866 dengan signifikansi sebesar p=0.000 (p>0.05). Artinya terdapat hubungan yang signifikan antara variabel nilai kebangsaan dengan sikap prososial.